Lung Function Status of Workers Exposed to Welding Fume: A Preliminary Study - Mulyana Mulyana; Nuri Purwito Purwito Adi; Meily L Kurniawidjaja; Andi Wijaya; Irawan Yusuf (The Prodia Education and Research Institute (PERI), 2016)
BACKGROUND: Exposure to welding fume in the workplace was associated with lung function disorders and occupational asthma. In this study, we determined lung function parameters in men workers exposed to welding fumes from heavy equipment manufacturer. This study is a preliminary study of biomonitoring program in worker exposed to welding fume as our main study. METHODS: A study with case-control design, random study, was conducted among welder (59 subjects) and non-welder (34 subjects) with more than one year experience in the same job task in a heavy equipment manufacturer. All subjects completed physical examination, informed consent, questionnaire and lung function status. Lung function status was measured by spirometer with vital capacity (VC), forced vital capacity (FCV), forced expiratory volume in one second (FEV1) and ratio of FEV1/FVC as test parameters. Linear regression model was developed to identify the risk factor of lung function parameter status using age, working period and smoking status as variables. RESULTS: This study showed that there were significant lower VC, FVC and FEV1 in welder than non-welder, but not difference in ratio of FEV1/FVC. However, there was no significant difference among welder from foundry and fabrication plan. By multivariate analysis, working period was found as a risk factor for lower parameters in lung function among welder. CONCLUSION: Lung function parameters status were significantly lower in welder than non-welder, and working period was the most important indicator for lung function status evaluation among welder. KEYWORDS: vital capacity, VC, forced vital capacity, FCV, forced expiratory volume in one second, FEV1, lung function, ratio of FEV1/FVC, working period